16QAM Vector Millimeter-Wave Signal Generation Based on Phase Modulator With Photonic Frequency Doubling and Precoding - Lun Zhao; Jianguo Yu; Lei Chen; Ping Min; JiaHeng Li; Renfan Wang (IEEE Photonics Journal)
In this paper, we experimentally demonstrate a method to generate a frequency-doubling photonic 16-quadrature-amplitude-modulation (16QAM) vector millimeter-wave (mm-wave) signal by using a single phase modulator (PM) with an amplitude and phase precoding technique. The PM is driven by a 2-Gbaud 16QAM-modulated precoded vector signal at 20 GHz. We transmit the generated optical radio-frequency (RF) signal at 40 GHz over 22-km single-mode fiber, and after heterodyne beating in a single-ended photodiode, a 40-GHz electrical vector mm-wave signal displaying regular 16QAM modulation can be generated with a bit error ratio (BER) of less than the hard-decision forward error correction (HD-FEC) threshold of $3.8× 10^{-3}$ . To our knowledge, this is the first time that high-order QAM vector mm-wave signal generation based on a single has been demonstrated.